Speel die Bybel nog 'n rol in die Praktiese Teologie? - J. Janse van Rensburg (Acta Theologica)
It may seem strange that the question is asked: Does the Bible play a significant role in the scientific activities of Practical Theology? Is it possible that a theological discipline, dealing with the practical work of the Church, could ignore the importance of a Biblically based theological theory? There are indeed many variables that could influence Practical Theology in this regard. It could therefore be both necessary and rewarding to investigate this question in more detail.